Pelestarian Biodiversitas Buah Lokal dan Upaya Pelestariannya oleh Masyarakat di Kabupaten Kampar, Riau - Nurnatasya, Nurnatasya; Titisari, Prima W. (Jurnal Biologi Papua, 2023)
The biodiversity of fruiting plants that grow in various regions in Indonesia is a priceless wealth. Fruiting plants that grow in Indonesia and are planted by Indonesians are called local fruits. This study aimed to identify the types of local fruit that were used by the community and their conservation efforts. The research was conducted in 21 villages in Kampar district. The data was collected through FGDs with local community groups and interviewed with key informants such as village heads, traditional leaders, and community members who owned these local fruit trees. The results showed that there were 12 species of local fruit found in the sample area, namely: Copper Durian (Durio zibethinus L.), Tampui (Baccaurea macrocarpa), Duku (Lansium domesticum Corr.), Mangosteen (Garcinia mangostana L.), Kuwini (Mangifera odorata), Cempedak Hutan (Artocarpus integer), Kapulasan (Nephelium mutabile Blume.), Rambutan (Nephelium lappaceum L.): (2 varieties, Kapulasan and Rambutan), Guava: Guava (Psidium guajava) and Guava Bol (Syzygium malaccense (L.) Meer): (2 varieties: guava and guava bol), Sawo Manila (Manilkara zapota), Rambai (Baccaurea motyryana Mull.Arg.), Breadfruit (Arthocarpus altilis Fosberg.), Belimbing Wuluh (Averrhoa bilimbi L.) and Ciplukan (Physalis angulate L.). These fruits provided many benefits for the community, not only as a source of vitamins for the family, but also as an additional income for the family economy. Culturally, conservation efforts were carried out by the community replanting and maintaining these plants properly. For the process of plant propagation, the community built nurseries and provided fertilizer for plant nutrition, while the place for planting plants used land such as plantations and in the community's yard.  Key words: fruit biodiversity; local fruits; conservation